Optical Coherence Tomography for Diagnosis and Treatment of Corneal Diseases - N. V. Fisenko; G. A. Osipyan (Oftalʹmologiâ)
Optical coherence tomography (OCT) is a modern non-contact real-time imaging of anterior and posterior eye’s segments. Based on the principle of low-coherence interferometry, it provides the analysis of tissue structures. In this review, we discuss technical aspects of two different OCT platforms: Time-Domain OCT (TD-OCT), and Spectral-Domain (SD-OCT) with the use of Fourier transformation — Fourier-Domain (FD-OCT). Over the last several years, the development of OCT has increased the resolution of images by different ways of optical filtering. The usage of tunable swept laser instead of superluminescent diode in modern Swept-Source OCT (SS-OCT) provides the sufficient quality of image. Anterior segment OCT can detect the pathological changes in different ocular structures and may be a key tool for monitoring of their progression. In pterygium OCT shows the true extent of fibrovascular granulation tissue in stromal layers, whereas in keratitis it provides imaging of corneal infiltration. Frequently, OCT-pachymetry can be advantageous in the detection of subclinical keratectasias. In patients with bullous keratopathy OCT can help to distinguish corneal edema and fibrosis. The new era of OCT is characterized by application of this method in keratorefractive surgery. Microscope-mounted (portable) and microscopeintegrated OCT systems have been developed. During LASIK surgery intraoperative OCT (iOCT) helps to assess flap interface, measure flap and residual bed thickness. It is a useful tool to reveal the structural changes during corneal collagen crosslinking. At the beginning of keratoplasty, iOCT helps to determine the corneal thickness, extent and depth of opacity, Descemet membrane perforation. iOCT guides decision-making regarding keratoplasty modification, depth and diameter of trephination. Furthermore, a real-time visualization of ocular structures during keratoplasty decreases the frequency of intra- and postsurgical complications.